Engineering-ecological research of the upper part of geological section using seismic data - О.К. Тяпкін; С.А. Онищенко; О.В. Піскунов (Геофизический журнал, 2025)
The paper presents the results of reprocessing seismic data typically lost during hydrocarbon exploration. These data are used to map the velocity properties (longitudinal wave velocities) of the upper part of the geological section, to reduce costly engineering and survey work for industrial and civil construction, and to promote the successful development of precise agriculture in oil and gas regions. Additionally, the study addresses the average shear-wave velocity in the top 30 m of the Earth’s surface (Eqn001.wmf) for seismic risk assessments and to solve engineering-hydrogeological challenges.